Check Your Truth Conditions! Clarifying the Relationship between Theories of Causation and Social Science Methods for Causal Inference. (November 2021) - Rohlfing, Ingo; Zuber, Christina Isabel
Theories of causation in philosophy ask what makes causal claims true and establish the so-called truth conditions allowing one to separate causal from noncausal relationships. We argue that social scientists should be aware of truth conditions of causal claims because they imply which method of causal inference can establish whether a specific claim holds true. A survey of social scientists shows that this is worth emphasizing because many respondents have unclear concepts of causation and link methods to philosophical criteria in an incoherent way. We link five major theories of causation to major small and large- n methods of causal inference to provide clear guidelines to researchers and improve dialogue across methods. While most theories can be linked to more than one method, we argue that structural counterfactual theories are most useful for the social sciences since they require neither social and natural laws nor physical processes to assess causal claims.